A correlative study of dental age and skeletal maturation - Kiran Sachan; Vijay Prakash Sharma; Pradeep Tandon (Wolters Kluwer Medknow Publications, 2011)
Introduction: Skeletal age had been assessed by comparison between maturation of hand-wrist with stages of cervical vertebrae or canine calcification stages in past and this had been closely related to craniofacial growth. The importance of pubertal growth spurt in various types of orthodontic therapies is already established. Aims and Objectives: Hence, this study was aimed to evaluate the relationship of skeletal maturity by hand-wrist with cervical vertebral maturation indicators and canine calcification stages. Materials and Methods: The study consisted of randomly selected 90 children from Lucknow population with 45 males (age range 10-13 years) and 45 females (age range 9-12 years). Lateral Cephalogram, hand-wrist x-ray, and periapical x-rays of maxillary and mandibular right canines were taken. Statistical Analysis: Mean, standard deviation was calculated of different groups. Correlation was made among cervical vertebral maturation, hand wrist maturation, and canine calcification stages at various age groups. Results: There was strong correlation between skeletal maturation indicator and cervical vertebral maturation indicator for both male (0.849) and female (0.932), whereas correlation between skeletal maturation indicator and canine calcification was good for both male and female (0.635, 0.891). Conclusion: It was concluded that cervical vertebral maturation indicator and canine calcification stages can also be used for assessing skeletal maturity.